2005
DOI: 10.3168/jds.s0022-0302(05)72920-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Induced Clinical Mastitis During Preovulation on Endocrine and Follicular Function

Abstract: The objective of the study was to determine if experimentally induced clinical mastitis before ovulation resulted in alterations of endocrine function, follicular growth, or ovulation. On d 8 (estrus = d 0), cows were challenged (TRT; n = 19) with Streptococcus uberis or were not challenged (control; n = 14). Forty-eight hours after induction of luteal regression on d 12, blood samples were collected to determine estradiol-17beta, LH pulse frequency, and occurrence of the LH surge. Ovaries were scanned to moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 24 publications
2
34
1
1
Order By: Relevance
“…Per-rectum ultrasonographic measurements of both follicular growth and maximum diameter were similar to other studies in postpartum cows [23–25], and concurred with results after experimentally induced mastitis [26]. Nevertheless, the present study is the first to show that ovulation is detrimentally affected.…”
Section: Discussionsupporting
confidence: 92%
“…Per-rectum ultrasonographic measurements of both follicular growth and maximum diameter were similar to other studies in postpartum cows [23–25], and concurred with results after experimentally induced mastitis [26]. Nevertheless, the present study is the first to show that ovulation is detrimentally affected.…”
Section: Discussionsupporting
confidence: 92%
“…This was in close agreement with a study by Wilson et al (2008). Similarly, Hockett et al (2005) found that cows experimentally infected with Strep. uberis were more likely to exhibit signs of impaired reproductive performance, including lack of Table 5.…”
Section: Discussionsupporting
confidence: 88%
“…When CM occurs before AI, the reproductive system may be too impaired to initiate a pregnancy, due to estrus cycle disruptions (Hockett et al, 2005;Williams et al, 2008;Herath et al, 2009). Alternatively, even if the embryo does successfully implant in the uterus, it may be lost before pregnancy is confirmed (Moore et al, 2005).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It was shown that clinical mastitis has multiple actions that hinder normal endocrine function and particularly affecting communication from the pituitary to the ovary (Hockett et al 2005). The onset of clinical mastitis was also important in terms of embryo survival Hertl et al 2010).…”
Section: Introductionmentioning
confidence: 99%